An oculocerebral hypopigmentation syndrome: a case report with clinical, histochemical, and ultrastructural findings. Issue 2 (February 1987) - Patton, M A; Baraitser, M; Heagerty, A H; Eady, R A
Abstract : A 4 year old boy is reported with tyrosinase positive hypopigmentation, mental retardation, ataxia, and myopia. Radiological investigation showed occipital cerebral atrophy, coxa valga, and generalised osteoporosis. The skin histology and electron microscopy are reported and discussed. The clinical features are similar to those of the oculocerebral hypopigmentation syndrome described by Preus et al.